Migration criminality in the modern megapolis: risk management - T. N. Yudina; T. M. Bormotova (Управление)
The existence interrelationship between migration and criminality is one of the controversial issues, rising in the discussion of migration processes. The authors propose to consider immigration criminality as a mass social, legal, socially dangerous phenomenon, consisting of the totality of crimes, committed by migrants in various spheres of life of the region, ensure personal and public safety of its population, public order. The risks of migration criminality in the modern Russian metropolis, as well as their perception and evaluation of representatives of society are the basis of appearance of social tension and can increase the level of conflict between local people and newcomers. Certain causes and conditions specific criminal activities, laying on the social, economic factors of migration exert a criminogenic influence on migrants. At the risk of the migration criminality the authors in their study propose to distinguish the extent possible danger caused by migration processes, directly affecting the stability and well-being crime, living in a certain area of people.The article also presents the main results of author’s sociological research of the risks of migration criminality, which are based on studies of subjective evaluations of residents of the Moscow megapolis and experts, representing 4 groups of experts: heads of departments of the Moscow government, representatives of public organizations, law enforcement agencies and the media. The risks of migration criminality have identified and described in the study. The performed analysis has allowed us to formulate the basic suggestions for minimizing the risks of migration criminality. These proposals require special attention and further scientific reflection with further improvement of the migration policy of Moscow.